Oral dantrolene reduces myalgia and hyperckemia in a child with RYR1-Related Exertional Myalgia/Rhabdomyolysis - Silva, Elis Vanessa de Lima (2023)
RYR1-related exertional myalgia/rhabdomyolysis (ERM) is an underrecognized condition, which can cause limiting muscle symptoms, and may account for more than one-third of undiagnosed rhabdomyolysis cases. Dantrolene has shown promising results in controlling muscle symptoms in individuals with ERM, however, its use in children remains poorly documented. This case report presents the successful treatment of a 5-year-old patient with ERM using oral dantrolene. The patient experienced notable improvements, including a reduction in the frequency and intensity of myalgia episodes, no hospitalizations due to rhabdomyolysis, a substantial decrease in creatine phosphokinase (CPK) levels, and enhanced performance on the 6-minute walk test. The use of dantrolene was well-tolerated, and no significant adverse effects were observed. This report adds to the existing evidence supporting the effectiveness of oral dantrolene in managing ERM, and, to the best of our knowledge, this is the first report of the use of dantrolene in a pediatric patient for controlling anesthesia-independent muscle symptoms.